Paligenosis: prepare to regenerate!. (22nd March 2018) - Messal, Hendrik A; Cremona, Catherine A; Lan, Linxiang; Behrens, Axel
Abstract : Tissue injury can stimulate quiescent cells to proliferate, resulting in metaplasia, to rapidly replace damaged cells and enable regeneration. A new study describes how fully differentiated cells return to proliferation in an autophagy‐ and mTORC1‐dependent manner. Given the striking parallels between this process in mammalian stomach and pancreas, a new term, paligenosis, is proposed for this conserved program. Abstract : Differentiated cells in stomach and pancreas return to proliferation in an autophagy‐ and mTORC1‐dependent manner to enable efficient tissue renewal.